15 Diagnostic utility and safety of coronary ct angiography in pre-renal transplant patients. (15th May 2019) - Voon, Victor; O'Reilly, Nanci; Hawkins-VanDerCingel, Gerlineke; Pugliese, Francesca; Cheasty, Emma; Ashman, Neil; Davies, Ceri
Abstract : Background: Emerging evidence suggests a potential role of coronary computed tomography angiography (CCTA) for coronary assessment pre-renal transplantation. Therefore, we aimed to evaluate the diagnostic utility and safety of CCTA in such patients. Methods: We retrospectively evaluated data from 58 consecutive patients who had pre-renal transplant CCTA between 2010-2018. The diagnostic value of non-obstructive (<70% stenosis) and obstructive (≥70% stenosis) coronary artery disease by CCTA in predicting subsequent myocardial infarction (MI) and/or percutaneous coronary intervention (PCI) was assessed. Results were expressed as mean±SD. Results: Mean age of patient cohort was 50±11 years old with a follow-up duration of 46±20 months from CCTA. Baseline demographics include male (58%), hypertension (65%), diabetes (42%), hemodialysis (70%), peritoneal dialysis (18%), not on dialysis (12%). Among those not on dialysis, no patients experienced contrast-induced nephropathy post-CCTA. All patients subsequently underwent renal transplant. CCTA demonstrated mean DLP 503±535 mGym 2 and calcium score 167±309. Number of patients with obstructive coronary disease: 1-vessel (n=5), 2-vessels (n=6), 3-vessels (n=1). Independent of symptoms, CCTA demonstrated a positive predictive value 41%, negative predictive value 100%, sensitivity 100%, and specificity 86%, in predicting subsequent MI/PCI over the follow-up period. Conclusion: In this cohort of pre-renal transplant patients, CCTA is safe, and has a high sensitivity and negative predictive value in ruling out obstructive coronary disease and subsequent MI/PCI over a 4-year follow-up period. CCTA also acts as a valuable diagnostic gatekeeper prior to subsequent functional and/or invasive testing.